15ᵀᴴ CONGRESS OF FINNO-UGRIC WRITERS - WALCZ, Beatrix (Studia Universitatis Babeș-Bolyai Philologia, 2019)
„The rocks we have seen on our way, remember such stories that even the eldest among us cannot know.” These words of an old Khanty woman concisely describe the profound experience that we could feel as participants or organisers of the 15th Congress of Finno-Ugric Writers, held in the cultural centre of Transylvania, Cluj-Napoca (Kolozsvár) between 21st −25th August 2019. This congress was characterised by an astonishing ambiguity. On the one hand, we could hear some scientific-informative, but also personal presentations about being a writer, poet or editor in the diaspora. On the other hand, besides the purely intellectual part of the congress we could also experience some more basic and spiritual layers with our various language relatives.